The Contemporary Japanese Imagination in Makoto Shinkai's Tenki no Ko - Muslimah Nur Irfan; Lina Meilinawati Rahayu; Amaliatun Saleha (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
Makoto Shinkai’s Tenki no Ko (2019) presents a narrative that moves across urban spaces shaped by modern technology, social pressure, and ecological instability, a movement that is closely experienced by its characters as they navigate everyday life in contemporary Japan. This study focuses on how Japan is imagined in Tenki no Ko and how that imagination presents utopia as a form of critique of contemporary Japanese society. The analysis uses a qualitative descriptive approach using the semiotics of Ferdinand de Saussure to reveal the relationship between signs in the text and the representation of modern Japan. The meaning of these signs is then connected to Ernst Bloch’s theory of utopia to see how hope and future possibilities are shown in the narrative. By combining these two frameworks, this study examines Tenki no Ko not only as a critique of Japan’s social and ecological conditions but also as presenting utopia as an ongoing process. The findings show that Tenki no Ko offers a critique of modernity while presenting utopia not as a perfect final world. Instead, utopia appears as a form of hope that grows from human relations with the city and with nature. From this analysis, the article argues that Tenki no Ko functions both as a critique of modernity and as an imaginative space where alternative ways of coexisting with nature in contemporary Japan can be continuously negotiated.